PENGARUH TINGKAT PENGUNGKAPAN INTELLECTUAL CAPITAL TERHADAP ROA PADA PERUSAHAAN PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BEI DARI TAHUN 2010-2014 - Amalia, Vera (LPPM Universitasdiwangsa Jambi, 2020)
This study was conducted to disclose and analyze the effects of the Intellectual Capital Disclosure which was measured by the content analysis methods with the Operational Efficiency Ratio (OER), and Loan to Deposit Ratio (LDR) on the profitability (ROA) of the Conventional Banks in Indonesia Stock Exchange. The data used in this study were obtained from the Annual Reports Published by the Conventional Banks on the IDX websites. The sources of the data in this study were the Conventional Banks operating in Indonesia with the greatest assets during the period of 2014. Thirteen banks were selected to be the subjects of the study which satisfied the desired criteria, with the observation period from 2010 to 2014. The method of the study used was the panel data regression analysis, in which the data were previously examined with the classical assumption tests including the data normality, heteroskedasticity, ulticollinearity and autocorrelation tests. The results of observation showed that the data of the study were normally distributed. The results of the data normality test, multicollinearity test, heteroscedasticity test and autocorrelation test did not show any deviation from the classical assumptions. The partial results of the study showed that the variable of the ICD had a positive and significant effect on the Return on Assets (ROA), the variable of the Operational Efficiency Ratio (OER) had a significant negative effect on the ROA, while the LDR variable had an insignificant negative effect on the ROA. The value of the coefficient of determination (R square) was 99.10%, which meant that simultaneously ICD, OER, and LDR had an effect of 99.10% on the Return on Assets (ROA) of the Conventional Banks in the Indonesia Stock Exchange.